Proton-Conducting La-Doped Ceria-Based Internal Reforming Layer for Direct Methane Solid Oxide Fuel Cells - Zhao, J.; Xu, X.; Zhou, W.; Blakey, I.; Liu, Shaomin; Zhu, Z. (American Chemical Society, 2017)
Performance degradation caused by carbon deposition substantially restricts the development of direct methane solid oxide fuel cells (SOFCs). Here, an internal reforming layer composed of Ni supported on proton conducting La-doped ceria, such as La2Ce2O7 (LDC) and La1.95Sm0.05Ce2O7 (LSDC) is applied over conventional Ni-Ce0.8Sm0.2O2-x (SDC) anodes for direct methane SOFCs. The proton conducting layer can adsorb water for internal reforming thus significantly improving the performance of the direct methane SOFCs. In situ Raman and FTIR results confirm the water adsorption capacity of LDC and LSDC. They also exhibit excellent phase stability in wet CO2 at 650 °C for 10 h, which ensures that the additional catalyst layer maintains structure stability during the internal reforming. In wet methane at 650 °C, the peak power density of the conventional cell is only 580 ± 20 mW cm(-2), and increases to 699 ± 20 and 639 ± 20 mW cm(-2) with the addition of Ni-LDC and -LSDC layers, respectively. For the stability test in wet methane at 650 °C and 0.2 A cm(-2), the voltage of the conventional cell starts to drop dramatically in 10 h, while the Ni-LDC and -LSDC catalyst layers operate stably in 26 h under the identical conditions. These catalyst layers even show comparable stability in dry and wet methane in 26 h, but for longer operation, the wet methane is still preferred for maintaining the stability of the cell.